Edaphological characterization in a blue agave (Agave tequilana Weber) cultivation in Tonaya and Tuxcacuesco, Jalisco, Mexico - Fregoso-Zamorano, Blanca Elizabeth; Mancilla-Villa, Oscar Raúl; Guevara-Gutiérrez, Rubén Darío; Moreno-Hernández, Arturo; Figueroa-Bautista, Pedro; Can-Chulim, Álvaro; Hernández-Vargas, Omar; Cruz-Crespo, Elia; Ortega-Escobar, Héctor Manuel; Khalil Gardezi, Abdul; Villalvazo-López, Víctor Manuel (REVISTA TERRA LATINOAMERICANA, 2023)
The cultivation of blue agave has economic importance in the state of Jalisco as it generates employment, being the main economic source in several municipalities such as Tonaya and Tuxcacuesco. However, at present, the edaphological status of the soils is unknown and there is limited knowledge on the factors that regulate crop growth, which limits the determination of optimal crop yields. In this sense, the aim of our research was to evaluate the state of fertility of the soils cultivated with blue agave in plots with different characteristics (virgin and with several planting cycles), as well as to diagnose their status in the Tonaya and Tuxcacuesco municipalities in order to suggest more efficient management and nutrition practices. After analyses in the laboratory, the results show that the soils presented a mean pH value of 7.7, the mean concentration of organic matter was 2.19%. Overall deficiencies of nitrogen, phosphorus and potassium were found, thus, the soils were classified in the low‑to‑poor category in terms of nutritional content. Moreover, there were no significant differences between the plots evaluated, organic matter content and nutrients. We recommend the use of organic fertilizers and bean/corn/agave polyculture when agricultural and economic resources are sufficient.